Advances in IgA glycosylation and its correlation with diseases - Ding, Li; Chen, Xiangqin; Cheng, Hongwei; Zhang, Tiantian; Li, Zheng (Frontiers in Chemistry, 2022)
Immunoglobulin A (IgA) is the most abundant immunoglobulin synthesized in the human body. It has the highest concentration in the mucosa and is second only to IgG in serum. IgA plays an important role in mucosal immunity, and is the predominant antibody used to protect the mucosal surface from pathogens invasion and to maintain the homeostasis of intestinal flora. Moreover, The binding IgA to the FcαRI (Fc alpha Receptor I) in soluble or aggregated form can mediate anti- or pro- inflammatory responses, respectively. IgA is also known as one of the most heavily glycosylated antibodies among human immunoglobulins. The glycosylation of IgA has been shown to have a significant effect on its immune function. Variation in the glycoform of IgA is often the main characteration of autoimmune diseases such as IgA nephropathy (IgAN), IgA vasculitis (IgAV), systemic lupus erythematosus (SLE), and rheumatoid arthritis (RA). However, compared with the confirmed glycosylation function of IgG, the pathogenic mechanism of IgA glycosylation involved in related diseases is still unclear. This paper mainly summarizes the recent reports on IgA’s glycan structure, its function, its relationship with the occurrence and development of diseases, and the potential application of glycoengineered IgA in clinical antibody therapeutics, in order to provide a potential reference for future research in this field.